Understanding consumption patterns of vulnerable Costa Rican households through price and income elasticities in food - Erick Enrique Sequeira Benavides; Juan Rafael Vargas Brenes; Yanira Xirinachs Salazar (Población y Salud en Mesoamérica)
This study examines food consumption patterns in Costa Rica by estimating the income and price elasticities of food products among vulnerable households. Using data from the Encuesta Nacional de Ingresos y Gastos de los Hogares for 2004, 2013, and 2018, it applies a DLQ equation model with Cragg’s method to address zero expenditures. Unlike previous studies, which have primarily focused on broader economic sectors, this research provides a product-level analysis while also examining changes over time and emphasizing low-income households. The findings reveal that most food products are perfectly inelastic in both income and price, indicating that vulnerable households do not adjust their food consumption despite economic fluctuations. As a result, they absorb the impact of rising prices or declining incomes, at the expense of other essential goods and services. These rigid consumption patterns highlight structural economic constraints and reinforce the need for policies that mitigate the adverse effects of economic shocks on food security and poverty reduction.